2021
DOI: 10.1177/1591019921991397
|View full text |Cite
|
Sign up to set email alerts
|

The Woven Endobridge as a treatment for acutely ruptured aneurysms: A review of the literature

Abstract: The Woven Endobridge (WEB; Microvention, Aliso Viejo, California, USA) is a relatively new device which has been shown to be safe and effective for the treatment of wide necked bifurcation aneurysms in multiple prospective Good Clinical Practice studies. However, the vast majority of aneurysms included in these studies have been unruptured. The aim of this review is to summarise the current evidence available on the treatment of ruptured aneurysms with the WEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…As such, the WEB can be used to treat un- ruptured and ruptured aneurysms. 16,17,[21][22][23][24][25][26][27] To date, the four European GCP studies and the USA have included a relatively small number of ruptured aneurysms: 6.0% in WEB-IT and 8.3% in the three European GCP studies. 16,17 Several series and meta-analyses have recently focused on ruptured aneurysm management with WEB, showing its good efficacy in preventing rebleeding (see below).…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the WEB can be used to treat un- ruptured and ruptured aneurysms. 16,17,[21][22][23][24][25][26][27] To date, the four European GCP studies and the USA have included a relatively small number of ruptured aneurysms: 6.0% in WEB-IT and 8.3% in the three European GCP studies. 16,17 Several series and meta-analyses have recently focused on ruptured aneurysm management with WEB, showing its good efficacy in preventing rebleeding (see below).…”
Section: Indicationsmentioning
confidence: 99%
“…16,17 Several series and meta-analyses have recently focused on ruptured aneurysm management with WEB, showing its good efficacy in preventing rebleeding (see below). [21][22][23][24][25][26][27] In a recent meta-analysis, Essibayi et al 27 reported a rate of late rebleeding of 1.1%. Yet, there have been very few studies analyzing the role of WEB treatment versus other EVT techniques when managing ruptured aneurysms.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the decision to use a WEB over other forms of embolization was based on our belief that the WEB would require less procedural time along with promising results from recent literature examining the WEB in acutely ruptured cases and sidewall and communicating segment ICA aneurysms (note however, the time gained with a single WEB device was likely conceded due to the eventual time that retrieval mandated, which was obviously unintentional and unknown prior to treatment). [6][7][8][9] Goertz et al 7 showed complete occlusion in 76.5% of ICA sidewall aneurysms treated with WEB, without procedure-related morbidity or mortality, while Aguiar et al 8 showed a high safety profile for WEB devices when used in off-label indications such as posterior communicating artery aneurysms. While primary coil embolization, balloon-assisted coil embolization, and open surgical clipping were also considered as reasonable treatment options, we felt that WEB embolization was, at a minimum, not inferior to those techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, four systematic reviews and meta-analyses regarding the use of the WEB in the acute phase of ruptured aneurysm have been published 16–19. While using similar search strategies and inclusion criteria, different studies were included in the respective reviews.…”
Section: Woven Endobridge (Web)mentioning
confidence: 99%